Autodefensor - os direitos e deveres - Colosso, Karen; Bernardo, Lucia Valerio da Silva; Souza, Rosilma de; Almeida, Sandra Nunes de; Verão , Sidnei de Oliveira e Silvana Pedrosa; Carraro, Marcia Regina Simpioni (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> VER PDF